The Janus face of proliferating plasmablasts in dengue and COVID-19 infections - Nayak, Priya; Mukund, Kavitha; Subramaniam, Shankar (Frontiers in Immunology, 2023)
To investigate the B cell response in both dengue fever and COVID-19, we analyzed age-controlled (pediatric and adult), peripheral blood mononuclear cell scRNAseq datasets from patients infected with either dengue (primary or secondary) or COVID-19 (non-severe or severe). Our analysis showed that pediatric patients with dengue and adults with COVID-19 had an expanded proliferative plasmablast (p-PB) population. By contrast, neither the adults with dengue nor the children with COVID-19 in our dataset had p-PBs. To better understand the mechanisms that surround the emergence of p-PB populations in the circulation, we used these disease conditions as a model, and focused on naive B and memory B cells, as well as plasmablasts. In age/disease conditions with and without p-PBs, we found differences in cell sensing and activation, including via the B cell receptor and downstream signal transduction. Likewise, inflammation was mediated differently: relative to groups without p-PBs, those with p-PBs had increased expression of interferon response and S100 genes (particularly severe COVID-19). Furthermore, several transcription factors at the nexus of activation, inflammation, and cell fate decisions- and that could therefore influence p-PB generation- were expressed differently in groups with and without p-PBs. Further exploration of these mechanisms will have implications for immune memory, vaccine development, and post-viral autoimmune syndromes.